Ecological Observations of the Effects of Magnetized Water on the Fresh Water Snail Physa acuta (Draparnoud, 1805) (Baghdad Science Journal, 2025)
The freshwater Gastropod Physa acuta is an important species in fauna of aquatic habitats of Iraq. The species is considered a component of the food chain.The magnetized water is used in various fields; scientific, agricultural and industrial for different purposes. Exposure assays to magnetized water have so for revealed striking results. In the present investigation the species was exposed to 1000G magnetized water under laboratory conditions. The resulting effects were compared with those obtained from a control experiment where the individual kept in normal untreated water. Observations included growth as indicated by length, width and depth of snail shells as well as weight for both groups up to last day of snails life.Also ecological factors such as water temperature, PH, electrical conductivity, total dissolved solids were measured throughout the treatment. Animals exposed to 1000G magnetized water have shown significant response to control animals those not exposed to magnetized water. The total length of animals in millimeters for control and those exposed to intensity respectively (1.9-10)(1.83-12.43) and lengths of shell pore(1.3-7)(1.3-6.75)and wide shell pore (0.88-3.75)(0.83-6.85) and height shell(1-6)(0.95-5.75). The averages of body weight in gram for control animals and those exposed to intensity were respectively (0.1078)(0.1631).The results obtained in this study may be related to some important biological activities such as molecular and cellular during the growth period of the snails.